RENEWABLE HYBRID ENERGY PRODUCTION FOR RURAL SETTLEMENTS ANALYSIS AND DESIGN OF THE SYSTEM - ELNUR A.; OZLEM O. (Journal of Sustainable Energy)
Renewable energy systems are technologies that can generate electricity from solar, wind, hydroelectric, biomass, and other renewable energy resources. In the hybrid system design using the HOMER program, the energy generated by solar and wind energy is stored in batteries and used for loads when needed. The outputs of the PV panels and wind turbine used in the hybrid system are connected to a hybrid inverter that regulates the grid voltage and frequency, along with the batteries, and the loads are fed with the output from this inverter. In this study, a hybrid energy system capable of generating electricity from wind and solar energy is designed and implemented. The energy needs of 300, 700, 1000, 5000, and 20000 households in Baku city, Absheron region of the Republic of Azerbaijan were calculated using the HOMER program, and a hybrid renewable energy system was designed and analyzed to meet the needs. It is assumed that 4 people live in each household and accordingly, daily electricity use is calculated as 8.5 KWh/day per household.